Development of Canva-Based Digital Teaching Materials Integrated with Flipbook for Reading Comprehwnsion in Multigrade Classroom at CLC SD Ladong, Kuching, Serawak - Kaissa Melian; Supartinah Supartinah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Multigrade learning at CLC SD Ladong, Simunjan, Kuching, Sarawak still faces challenges related to the limited availability of teaching materials that meet students’ learning needs, which affects students’ reading comprehension skills. This study aimed to develop Canva-based digital teaching materials integrated with Flipbook that are feasible, practical, and effective in supporting reading comprehension learning. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of the stages of analysis, design, development, implementation, and evaluation. The research subjects were students in multigrade classes III and IV at CLC SD Ladong. Data were collected through observations, interviews, questionnaires, and reading comprehension tests. Product feasibility was evaluated through material and media expert validation, while practicality was measured through teacher and student response questionnaires. Effectiveness was analyzed using a one-group pretest–posttest design, followed by the Wilcoxon Signed Rank Test and N-Gain analysis. The findings revealed that the developed teaching materials achieved the category of highly feasible, with material expert validation scores of 61/70 and media expert validation scores of 73/80. Teacher responses reached 93% and student responses 97.2%, indicating a highly practical category. The Wilcoxon test results showed a value of Z = −4.429 with Asymp. Sig. (2-tailed) = 0.000 (< 0.05), indicating a significant improvement. The N-Gain score was 0.82 (81.7%), categorized as high. Therefore, the Canva–Flipbook-based digital teaching materials were proven to be feasible, practical, and effective in improving reading comprehension skills among multigrade students.